Alejandro Zaffaroni (1923–2014) - Shaw, Jane E. (Nature (London), 2014)
Alejandro Zaffaroni spent some 60 years helping to conduct research that led to the birth-control pill, and co-founded nearly a dozen biotechnology start-ups in California's Silicon Valley. He commercialized innovative ways to get drugs into the body. His adhesive skin patches, implanted devices and controlledrelease capsules reduced side effects, boosted efficacy and delivered the correct dose of medicine without complicated schedules.